ANALYSIS OF FINANCIAL STATEMENTS AS A TOOL FOR ASSESSING THE FINANCIAL PERFORMANCE OF PT PEMBANGUNAN PERUMAHAN (Persero) - Aditya Sri Yanto; Muhammad Yusuf (PERFECT EDUCATION FAIRY, 2023)
This study aims to analyze the financial performance of PT. Pembangunan Perumahan (Persero) Tbk in year of 2020, 2021 and 2022. This Study used liquidity ratios (current ratio and quick ratio), the solvency ratios (total debt to assets ratio and total debt to equity ratio), and profitability ratios (return on invesment and return on equity) as analysis tools. The results of current ratio and quick ratio research in 2020, 2021 and 2022 shows the company's financial condition is quite good, because the ratios are above the industry average. Based on the measuring of solvency ratios, the company can keep its financial ratios stable and at the industry level. Likewise with the profitability ratio, the company can maintain the company's income in the midst of a market that has not returned to normal and the calculation results remain above the industry average.